Pharmacist Mediated Assessment and Reporting of Adverse Drug Reactions in a Tertiary Care Hospital - Zia, Inamdar Syed; K, Pradeepthi; N, Ashwini; L, Soumyashree; R.V, Kulkarni (Indian Journal of Pharmacy Practice)
Background: ADRs are one of the foremost reasons of illness and death, adding to overall preventive medicine cost. Reporting of such adverse drug reactions are critical parameter of medical treatment. The present study assess the clinical pharmacist role in drug monitoring to detect and intercept adverse drug reaction in a health care setting, Method: A prospective observational was conducted at tertiary care hospital in Vijaypur city. A total of 50 suspected adverse effects were recognized and documented during the study period of six months. The suspected adverse effects were assessed for its causality and severity by using Naranjo’s and Hartwig’s scale. Results: Overall 50 ADRs were identified and documented during the study period. Most of the reported ADRs in this study were Type A 34(68%). Drug dose and frequency 18(33.96%), Age 15(28.3%) and polypharmacy 10 (18.86%) were the furthermost protruding predisposing factors of ADRs were observed. Antibiotics were the common class of drugs involved in producing ADRs 14(28%).Causality assessment by Naranjo’s scale presented that majority of the reported ADRs were found to be probable 26(52%), possible 19(38%) and definite 3 (6%). Severity assessment by Hartwig’s scale showed that 26(52%) ADRs were moderate, 17 (34%) ADRs were mild and 7(14%) ADRs were of severe. Withdrawal of the drug 27(54%) as a management intervention was the core line of the adverse drug effect management. Conclusion: Clinical Pharmacist preparedness towards pharmacovigilance approach and proximity for drug monitoring resulted in greater interception and reporting of adverse effect ensuring patient drug related safety.
Keywords: Adverse drug reaction; Pharmacovigilance; Severity; Causality; Clinical pharmacist.